2018
DOI: 10.3390/ijms19020427
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous, Smart, and Bioinspired Polyphosphate Nano/Microparticles: A Biomaterial for Regeneration and Repair of Osteo-Articular Impairments In-Situ

Abstract: Using femur explants from mice as an in vitro model, we investigated the effect of the physiological polymer, inorganic polyphosphate (polyP), on differentiation of the cells of the bone marrow in their natural microenvironment into the osteogenic and chondrogenic lineages. In the form of amorphous Ca-polyP nano/microparticles, polyP retains its function to act as both an intra- and extracellular metabolic fuel and a stimulus eliciting morphogenetic signals. The method for synthesis of the nano/microparticles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 81 publications
0
37
0
Order By: Relevance
“…The anionic polymer Na-polyP can be readily co-precipitated with the anionic zoledronic acid, a drug frequently used in management of metastatic bone diseases 201 in the presence of Ca 2+ . 188 During this process the mixed deposits Ca-polyP/zoledronic acid remain almost perfectly amorphous (Fig. 13E) like the Ca-polyP particles, in contrast to the deposits with pure zoledronic acid and Ca 2+ which formed strong crystals (Fig.…”
Section: Amorphous Polyp Particles As Drug Carriers: Zoledronic Acidmentioning
confidence: 97%
See 1 more Smart Citation
“…The anionic polymer Na-polyP can be readily co-precipitated with the anionic zoledronic acid, a drug frequently used in management of metastatic bone diseases 201 in the presence of Ca 2+ . 188 During this process the mixed deposits Ca-polyP/zoledronic acid remain almost perfectly amorphous (Fig. 13E) like the Ca-polyP particles, in contrast to the deposits with pure zoledronic acid and Ca 2+ which formed strong crystals (Fig.…”
Section: Amorphous Polyp Particles As Drug Carriers: Zoledronic Acidmentioning
confidence: 97%
“…13A and B). The expressions of the differentiation/transcription factor SOX9 (differentiation towards osteoblasts) and of the factor RUNX2 (chondrocyte differentiation) were used as markers; 188 Fig. 13.…”
Section: Activity Of the Various Slowly Soluble Polyp Salts In The Lomentioning
confidence: 99%
“… 26 More recently, calcium/polyP nanoparticles were also found to promote osteogenic and chondrogenic differentiation of bone marrow cells. 27 However, many fundamental questions remain, including how polyP is distributed intracellularly after uptake, if there is any difference in polyP uptake among different cell types, how stable polyP particles are to enzymatic degradation, and what the roles of polyP are in cellular function. In addition, these methods to deliver polyP afforded minimal or unreported levels of cellular delivery and are yet to enable widespread study of intracellular polyP signaling and function.…”
Section: Introductionmentioning
confidence: 99%
“…Inorganic polyphosphate (PolyP) is one of the molecules with pro-thrombotic and pro-inflammatory properties in the circulatory system [14,15] that recently has been reported as calcification enhancer of osteoblasts culture medium [16]. Our recent study showed that there is a RAGE-dependent poly P-mediated crosstalk between mTOR and the GSK-3/Wnt/b-catenin signalling network in endothelial cells [14], on the other hand, has been reported polyP can be an important role for repairing long bone osteoarticular damages [17].…”
Section: Introductionmentioning
confidence: 86%